Electrooxidative α-hydroxymethylation of ketones with dimethylformamide as the carbon source. Issue 8 (27th March 2023) - Zheng, Jin-Ming; Li, Yi-Fei; Pan, Yi-Xiang; Hu, Xiao-Dong; Ye, Xiao-Xia; Li, Ren-Hao
Abstract : We report the electrocatalytic α-hydroxymethylation of ketones using DMF as the carbon source at room temperature in air in a conversion that proceeds without need for toxic and expensive chemical oxidants or metal catalysts. Abstract : An environmentally benign electrochemical approach has been developed for the α-hydroxymethylation of ketones using N, N -dimethylformamide as the carbon source for the construction of β-hydroxy ketones. This method does not require metal catalysts or chemical oxidants and proceeded smoothly at room temperature to demonstrate tolerance of a broad range of functional groups.